Strategi Komunikasi Guna Meningkatkan Efektifitas Dakwah Mahasiswa Fakultas Dakwah UIN SMH Banten - Muhammad Ikrar Wiratama; Mutaji; Adhi Kusuma (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the academic communication strategies implemented by lecturers and students of the Faculty of Da'wah UIN Sultan Maulana Hasanuddin (SMH) Banten in increasing the effectiveness of campus da'wah. Using a qualitative approach and case study design, data were collected through in-depth interviews, participatory observation, and documentation of da'wah communication media. The results of the study indicate that the dialogic approach in learning, integration of digital media.This strategy not only improves students' communication competence, but also expands the reach of da'wah which is contextual and adaptive to the development of the times. The challenges faced include low media literacy of some students and limited digital infrastructure, but can be overcome through continuous training and mentoring. This study recommends strengthening the da'wah curriculum based on strategic communication competencies and developing digital da'wah media.